DIGITAL GEOPOLITICS IN INDONESIAN NETIZENS’ PERCEPTION TO THE 2025 IRAN-ISRAEL WAR - Maziar Mozaffari Falarti; Dina Yulianti; Muhammad Fikry Anshori; Deasy Silvya Sari; Otong Sulaeman (Intermestic: Journal of International Studies, 2026)
The “12-Day War” between Iran and Israel in June 2025 sparked broad discussions on social media platforms, such as among Indonesian users on X (previously known as Twitter). In this study, the conflict is analyzed in the context of digital geopolitics and the perception of the conflict by the Indonesian digital publics. The article examines online discourse regarding military concerns, humanitarian solidarity, religious identity, and geopolitical anxiety in the context of Indonesia as a large Muslim society and Global South society. The study employs the concept of digital geopolitics and uses a mixed-method approach combining IndoBERT-based sentiment analysis, unguided topic modeling, and qualitative interpretive reading. The data used is in the form of tweets in the Indonesian language with a total of around 3,000 tweets from 13 June to 24 June 2025. The results highlight three prevailing discourses: escalation and tactical warfare, religious-humanitarian solidarity with Palestine and public concerns about wider global instability. The sentiment against Israel was overwhelmingly negative, across a variety of issues. The study finds that the digital public sphere in Indonesia can be described as a geopolitical space that is decentralized and where international conflicts are understood by local moral language, religious identity, and political awareness of the Global South. The article is a valuable addition to the literature of digital geopolitics by highlighting the growing role of the digital publics in Southeast Asia in shaping transnational political discourse.